2016
DOI: 10.1016/j.cllc.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Computed Tomographic Features and Kirsten Rat Sarcoma Viral Oncogene Mutations in Patients With Stage I Lung Adenocarcinoma and Their Prognostic Value

Abstract: Background To investigate the association between computed tomographic (CT) features and KRAS mutations in patients with stage I lung adenocarcinoma and their prognostic value. Patients and Methods Seventy-nine patients with pathologic stage I lung adenocarcinoma, available KRAS mutational status, preoperative CT images, and survival data were included in the study. Seven CT features including spiculation, concavity, ground-glass opacity, bubblelike lucency, air bronchogram, pleural retraction, and pleural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
13
2
Order By: Relevance
“…As reported in previous research, guidelines for PMA therapy have not been clearly established, and additional research is needed to resolve this important question. Additionally, many studies had demonstrated that pleural invasion was significantly associated with an increased risk of survival . However, we observed that pleural invasion is a favorable prognostic factor in univariate analysis in our study; it indicates that pleural invasion has an interaction with another variable, such as AJCC stage and chemotherapy.…”
Section: Discussioncontrasting
confidence: 76%
“…As reported in previous research, guidelines for PMA therapy have not been clearly established, and additional research is needed to resolve this important question. Additionally, many studies had demonstrated that pleural invasion was significantly associated with an increased risk of survival . However, we observed that pleural invasion is a favorable prognostic factor in univariate analysis in our study; it indicates that pleural invasion has an interaction with another variable, such as AJCC stage and chemotherapy.…”
Section: Discussioncontrasting
confidence: 76%
“…These studies generally had small sample sizes, used subjective observer-dependent imaging descriptors, and did not perform robust external validation. For example, associations have been reported between textural imaging features and KRAS mutations in combined imaging modalities (CT, 18 F- FDG PET and dynamic contrast-enhanced CT) in colorectal cancer(25), and using CT in NSCLC(27,47), but within small cohorts (<100 patients), and, more importantly, without external validation, which is a critical component of radiomic analyses(9,10). Our analysis of radiomic features extracted from CT images found that they had relatively weak predictive power for KRAS, a result that we validated in an independent validation set, indicating a generally similar imaging phenotype for KRAS-positive and negative tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of radiomic features extracted from CT images found that they had relatively weak predictive power for KRAS, a result that we validated in an independent validation set, indicating a generally similar imaging phenotype for KRAS-positive and negative tumors. For instance, Wang et al, found a single semantic CT feature, tumor spiculation, to be associated with the presence of KRAS mutations in a single cohort of stage I lung adenocarcinoma patients(47). We found, however, that EGFR-positive and negative tumors exhibit distinct imaging phenotypes, allowing more sensitive and specific classification of tumor EGFR status.…”
Section: Discussionmentioning
confidence: 99%
“…Transl Lung Cancer Res 2017;6(1):68-75 tlcr.amegroups.com of any GGO (43,44,48) or GGO ratio (33). One study (45) revealed that KRAS mutations were more common in lesions with a lower GGO proportion.…”
Section: Molecular Pathology and Ct Featuresmentioning
confidence: 99%